2017
DOI: 10.1177/2324709617728526
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus-Human Rhinovirus: A Rare Cause of Acute Respiratory Distress Syndrome

Abstract: A 22-year-old Asian woman presented with respiratory distress, cough, and wheezing for 1 week. Prior history included asthma and Turner syndrome. On presentation to the emergency department, the patient was hypotensive, tachycardic, tachypneic, with an oxyhemoglobin saturation in the mid 80% range while breathing ambient air. Chest radiograph revealed pulmonary vascular congestion and a left lower lobe infiltrate. Endotracheal intubation, mechanical ventilation, and vasopressors were initiated. Empiric therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 10 publications
0
19
0
2
Order By: Relevance
“…20 Three case reports are reporting associations between HRV/HEV and ARDS in individuals under the age of 22 years have also been published. [29][30][31] Our study, in combination with previous data, highlights the importance of physicians being aware that children admitted with HRV/HEV, as the sole pathogen are at risk of developing pARDS.…”
Section: Discussionmentioning
confidence: 59%
“…20 Three case reports are reporting associations between HRV/HEV and ARDS in individuals under the age of 22 years have also been published. [29][30][31] Our study, in combination with previous data, highlights the importance of physicians being aware that children admitted with HRV/HEV, as the sole pathogen are at risk of developing pARDS.…”
Section: Discussionmentioning
confidence: 59%
“…There is no special medical treatment or vaccination, and the only option is supportive care in their self-limiting diseases (11). Moreover, recent studies and reports have demonstrated that this virus is not as innocent as presumed to be, which can cause life-threatening diseases (4)(5)(6)(7)(8). In a study from Vietnam, rhinovirus was detected in 12 children living in orphanages who were admitted to hospital due to severe LRTI between December 2007 and February 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, rhinoviruses can be detected as an agent in acute exacerbation in asthma, chronic obstructive pulmonary disease, and cystic fibrosis (2,3). It has been reported in recent studies that rhinovirus can cause LRTI with a high rate of malformation and mortality, acute respiratory distress syndrome (ARDS) and myocarditis along with self-limiting infections (4)(5)(6)(7)(8). Human herpes virus-7 (HHV-7) defined in 1990 for the first time can lead to exantem subitum, coryza, acute infantile hemiplegia, and hepatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia can lead to increased inflammation, as is observed in case of pneumonia presenting lungs ( Ngu et al, 2019 ). Prolonged inflammation can damage the lungs and therefore several immunocompromised as well as immunocompetent patients diagnosed with HRV infection develop shortness of breath, decreased oxygen saturation, severe acute respiratory distress syndrome (ARDS) and prolonged respiratory failure ( Ayala et al, 2019 ; Ngu et al, 2019 ; Soni et al, 2017 ; Gutman et al, 2007 ).…”
Section: Respiratory Virusesmentioning
confidence: 99%